Arthroscopic treatment of stable nonunion, unstable nonunion, or nonunion of the scaphoid with early degenerative radioscaphoid arthritis - Yin-chuan Shih; Chang-Chin Wu; Jui-Tien Shih (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background This study was designed to analyze the clinical follow-up results (minimum of 2 years) in patients with stable nonunion, unstable nonunion, or nonunion of the scaphoid with early degenerative radioscaphoid arthritis (Lichtman classification stage I–III) treated with arthroscopic osteosynthesis with autogenous bone graft. Methods We retrospectively recruited 44 consecutive patients with scaphoid fracture nonunion treated with arthroscopy-assisted percutaneous internal fixation with autogenous bone grafts from January 2010 to November 2019. We recorded union and return to activity and analyzed data with regular clinical follow-up at a mean duration of 33 months (range 24–46 months). Clinical (i.e., visual analog scale pain score, grip strength, and range of motion), radiographic, and functional (Mayo Modified Wrist Score (MMWS)) outcomes at the final follow-up were compared with the preoperative assessments and analyzed in patients with different stages. Results We confirmed union in 39 of the 44 patients (88.6%) after a mean 15.4 weeks post-operatively according to clinical examinations and standard radiography. All clinical parameters improved significantly. For the MMWS, there were 25 excellent and 14 good results. Of the 44 patients, 40 (90.9%) returned to work or sports activities at their preinjury levels. Comparisons of the outcomes between patients in different stages of scaphoid nonunion revealed no significant difference in the aspect of union rate, VAS pain score, and functional score improvement. Conclusions Arthroscopic osteosynthesis with autogenous bone grafts is a reliable and minimally invasive method for achieving nonunion healing and improving clinical outcomes in stage I–III scaphoid nonunion. Level of Evidence: Level IV, case series.